Pengaruh Edukasi Menggunakan Media PAPI GIZI terhadap Pengetahuan Gizi Seimbang Anak Sekolah Dasar - Wirawan, Susilo; Purnamasari, Dwi; Iskandar, Slamet; Aritonang, Irianton (Poltekkes Kemenkes Mataram, 2023)
Background. Obesity in children not only affects physical health but can also have an impact on mental health. Efforts that can be made to improve nutrition are by conducting nutrition education. Elementary school students are the best target in conducting nutrition education. In conducting nutrition education, interesting media are needed to attract students. Knowing the effect of nutrition education using PAPI GIZI media on balanced nutrition knowledge in elementary school children. Methods. This research is a Quasi Experiment research with pre test post test with control group design. This research was conducted on March 2023. The research locations were at SDN Perumnas Condongcatur (counseling using PAPI GIZI media) and SDN Babarsari (counseling using leaflet media), grade V for 52 students were selected. Statistical test data Saphiro Wilk, Wilcoxon Test, Mann Whitney. Result.The results showed that there was a significant influence by using PAPI GIZI media on knowledge about balanced nutrition (p = 0.000) and leaflet media on knowledge about balanced nutrition (p=0.001). There was a significant difference in the difference in knowledge scores on balanced nutrition in the PAPI GIZI group and leaflets (p = 0.002). The results showed that PAPI GIZI media and leaflets had an effect on increasing students' knowledge about balanced nutrition. Conclusion. PAPI GIZI media has a higher level of effectiveness compared to leaflet media in increasing knowledge about balanced nutrition in elementary school students.